2003
DOI: 10.1038/sj.ijo.0802471
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy weight gain from 1960s to 2000 in Finland

Abstract: OBJECTIVE:To study secular trends in average pregnancy weight gain between the 1960s and 2000 in Finland, and whether the changes were related to body mass index (BMI), age or parity. DESIGN: Three cross-sectional population surveys in Finland from three different periods. SUBJECTS: Women who were pregnant in Helsinki in the period 1954-1963 (N ¼ 2262), or in Tampere in the period 1985-1986 (N ¼ 1771) or in 2000-2001 (N ¼ 371). MEASUREMENTS: Pregnancy weight gain was determined from self-reported prepregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
0
31
2
4
Order By: Relevance
“…23 No Danish data for trend in GWG are available to quantify the potential contribution of GWG to the obesity epidemic, but a Finnish study reported an approximately 1 kg increase in mean GWG from the 1960s to the mid-1980s. 24 If this is associated with an 8% increase in obesity prevalence, as suggested by this study, we find this of great public health relevance.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…23 No Danish data for trend in GWG are available to quantify the potential contribution of GWG to the obesity epidemic, but a Finnish study reported an approximately 1 kg increase in mean GWG from the 1960s to the mid-1980s. 24 If this is associated with an 8% increase in obesity prevalence, as suggested by this study, we find this of great public health relevance.…”
Section: Discussionmentioning
confidence: 53%
“…All childhood BMI measurements were transformed to BMI Z-scores (BMI-Z), using the British 1990 growth references 20 for gender and exact age. For adults (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and 42 years), internal sex-specific BMI-Z was created to compare the results with those obtained in children. Analyses, including BMI at the draft board (16-23 years) and the first adult follow-up examination (20-34 years), were adjusted for current age.…”
Section: Variablesmentioning
confidence: 99%
“…Age distributions between these series were not equal, owing to an observed increase in median ages from 1983 to 2001. This is probably due to the increasing mean age of Finnish pregnant women [13]. Because of these observed differences, the series were further separated into the following age groups: less than 25 years, 25–30 and over 30.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] Both mean GWG and the proportions of high GWG have been found to be increasing over time in industrialised countries. 3,8,9 Several non-modifiable factors influence GWG: e.g. pre-pregnancy BMI, maternal age, height, parity and socio-economic status.…”
Section: Introductionmentioning
confidence: 99%